(untitled) (Herald of Journalism, 2016)
В статье автор рассматривает проблемы самостоятельной работы студентов как формы организации обучения в высших учебных заведениях с помощью технологии индивидуализации обучения. Показано историческое развитие идеи самостоятельной работы студентов и отдельные аспекты её организации в высших учебных заведениях, значимость самостоятельной работы для активизации учебно-творческой деятельности студентов. The problems of independent work as an organization form of education in higher educational institution with the help of individualization are raised. Historical development of ideas of students’ independent work and separate aspects of advantage organizing it in higher educational institutions are shown. The importance of organizing students’ independent work in special higher educational institutions for activation educational-creative activity is opened.